2011
DOI: 10.1111/j.1365-2923.2011.04101.x
|View full text |Cite
|
Sign up to set email alerts
|

Helping medical learners recognise and manage unconscious bias toward certain patient groups

Abstract: We propose a developmental model to illustrate how individuals might move from absolute denial of unconscious bias to the integration of strategies to mitigate its influence on their interactions with patients and offer recommendations to educators and education researchers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
141
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 157 publications
(143 citation statements)
references
References 53 publications
1
141
0
1
Order By: Relevance
“…Stone and Moskowitz (2011) have observed that implicit biases, although unconscious, may negatively influence how medical professionals interact with minority group patients. This, in turn, compromises health provider-patient rapport, fosters patient mistrust and dissatisfaction, and may ultimately lead to poorer healthcare (Teal, Gill, Green, & Crandall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Stone and Moskowitz (2011) have observed that implicit biases, although unconscious, may negatively influence how medical professionals interact with minority group patients. This, in turn, compromises health provider-patient rapport, fosters patient mistrust and dissatisfaction, and may ultimately lead to poorer healthcare (Teal, Gill, Green, & Crandall, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Examples include promoting awareness of one's own implicit biases and enhancing conscious efforts to overcome these biases (Burgess, Fu et al 2004, Burgess, van Ryn et al 2007, Teal, Gill et al 2012. In order for educational interventions that incorporate conscious awareness of implicit bias as an effective strategy, they must be designed to address a potential "kick-back" effect where individuals over-compensate and develop counter-biases in response to bias-eradication efforts (Ross 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Another potential cause of the racial gaps in proton therapy use is provider physician implicit bias; it has been demonstrated in pinnacle work on racial disparities that patient race influences provider decisions on treatment recommendations-a phenomenon that occurs with high predictive validity and that largely occurs at the unconscious level, and so is termed implicit bias. [21][22][23] It could be the case that providers might implicitly assume that minority patients are less able to afford the costs associated with proton therapy and/or that minority patients may be less likely to adhere to the treatment regimen of a form of therapy that still lacks level 1 evidence in terms of efficacy and so providers are less likely to recommend or push minority patients to receive proton therapy for prostate cancer. Unfortunately, implicit bias is difficult to study and would require physician surveys in order to determine the extent to which this phenomenon accounts for the gaps observed in this study.…”
mentioning
confidence: 99%